ANALISIS PEMBATALAN TRANSAKSI SETELAH KEBIJAKAN PELARANGAN TOUR GUBERNUR JAWA BARAT DI TINJAU DARI SISTEM IJARAH - Syafii, Moch (Bayani, 2025)
A transaction can be canceled for various reasons. This study analyzes the legal status of canceling tour package transactions due to a prohibition policy by the Governor of West Java from a Sharia perspective. Using a qualitative literature study method with the Siyasah Syar’iyyah (Arto, 2011) and Fikih Muamalah (Saleh & Dkk, 2023) approaches, this research examines the legitimacy of the policy and its legal consequences. The analysis results indicate that the policy is valid because it is based on public interest (maslahah ‘ammah) and constitutes a Sharia reason (‘udzur syar’i) (Hj. Anis Byarwati, S.Ag., 2011) for the cancellation (fasakh)(Tassia H, 2017) of an ijarah contract(Kristiyanto, 2008). The legal consequence is full restitution without compensation, in accordance with the principles of justice and the prohibition of causing harm.